The modified benjamin-bona-mahony equation via the extended generalized riccati equation mapping method - Naher, Hasibun; Abdullah, Farah Aini (© 2012 Applied Mathematical Science, 2016)
This article was published in the Applied Mathematical Sciences [© 2012 Hasibun Naher and Farah Aini Abdullah.] The Journal's website is at:http://www.m-hikari.com/ams/ams-2012/ams-109-112-2012/naherAMS109-112-2012.pdf